2022
DOI: 10.3390/rs14194922
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Performance and Case Study of Extreme Events in Northwest China Using the BCC-CSM2 Model

Abstract: The BCC-CSM2 model is the second generation of the Beijing Climate Center Climate System Model developed by the National Center of China Meteorological Administration. Using the outputs of two versions of the BCC-CSM2 model with different resolutions, namely: BCC-CSM2-MR and BCC-CSM2-HR, their performance in simulating the climate characteristics of Northwest China was compared. The BCC-CSM2-HR had a better ability to simulate the detailed distribution of the average temperature and precipitation in Northwest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…And this change also took place around 1986 [34]. In addition, the majority of prior research regarding extreme climate events in this region has shown that extreme climate events, such as storms and droughts, are becoming more frequent due to inhomogeneous precipitation [16,28,29,[35][36][37]. Whether the climatic extremes have changed in accordance with the changes of the average temperature and precipitation remains to be studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And this change also took place around 1986 [34]. In addition, the majority of prior research regarding extreme climate events in this region has shown that extreme climate events, such as storms and droughts, are becoming more frequent due to inhomogeneous precipitation [16,28,29,[35][36][37]. Whether the climatic extremes have changed in accordance with the changes of the average temperature and precipitation remains to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is imperative to gather more data regarding climate change from different countries and regions to make impactful decisions. Extreme climate events caused by climate change have been analyzed from regional [14][15][16][17][18][19][20] to global scales [21][22][23][24]. Regarding temperature extremes, there is a significant upward trend in nearly all regions.…”
Section: Introductionmentioning
confidence: 99%